Ответы и объяснения

2013-10-26T09:25:30+04:00
3* 5^{x+3} +2* 5^{x+1} =77
3* 5^{x}*5^{3} +2* 5^{x}*5 =77

пусть 5^{x}=y
375y+10y=77
385y=77
y=77/385=1/5

 5^{x} = \frac{1}{5}
 5^{x} =5^{-1}
x=-1

2.
(  \frac{1}{5}) ^{4x-y} =25
 7^{9x-y} = \sqrt{7}

( \frac{1}{5}) ^{4x-y}=  \frac{1}{5} ^{-2}
7^{9x-y} = 7^{ \frac{1}{2} }
составим новую систему
4х-у=-2
9х-у=1/2

у=4х+2
9х-4х-2=1/2

5х=5/2
х=1/2

у=4*1/2+2=4

3.
 4^{x} - 0.25^{x-2} =15
 4^{x} -  \frac{1}{4} ^{x-2} =15
 4^{x} - 4^{2-x} =15
заменим  4^{x}=y
y-16 y^{-1} =15
y-16/y=15
 y^{2}-15y-16=0
y=16
 4^{x} =16= 4^{2}
x=2